EPIDEMIOLOGY AND RISK FACTORS OF KIDNEY CANCER - Janout, Vladimír; Janoutová, Gabriela (Biomedical papers, 2004)
This review article presents kidney cancer epidemiology as well as main environmental and life style risk factors.
Keywords: Kidney cancer/Epidemiology/Risk factors